Transhiatal versus Left Transthoracic Esophagectomy for Gastroesophageal Junction Cancer; The Impact of Surgical Approach on Postoperative Complications - Mohammad Reza Mir; Marzieh Lashkari; Reza Ghalehtaki; Ali Mir; Amir Hossein Latif (Middle East Journal of Digestive Diseases, 2019)
BACKGROUND Esophagectomy is the mainstay of treatment for esophageal cancer. Although different surgical approaches have been described, choosing the most appropriate technique is still on debate. We compared the complications of transhiatal esophagectomy (THE) versus left transthoracic esophagectomy (LTE) among a group of Iranian patients with gastroesophageal junction cancer.